Clinical and epidemiological peculiarities of cervical precancer in female residents of Omsk - T V Klinyshkova; D V Turchaninov; I B Samosudova; T I Karatyuk (IP Berlin A.V., 2013)
Based the materials of an epidemiological sampling study of cervical precancer incidence it has been found: growth of primary CIN incidence (growth rate amounted to +7,9% according to the appealability data; p